IMPLEMENTASI PENETAPAN DESA ADAT DI MALUKU TENGAH - WITAK, SANTRI; MADUBUN, JUSUF (Patria Artha Management Journal, 2024)
ABSTRACT This research aims to determine the implementation of establishing traditional villages inCentral Maluku and to determine and analyze the inhibiting factors in the implementationof establishing traditional villages in Central Maluku. The type of research in thisresearch is qualitative research, with a total of 9 informants consisting of 3 heads of stateand 6 community leaders. Data collection techniques were carried out throughobservation, interview guidelines and documentation. The data analysis technique usesdescriptive analysis in the form of data reduction, data presentation, data verificationand drawing conclusions. The research results found that the implementation ofestablishing traditional villages in Central Maluku has not been optimal in terms of thesize and objectives of the policy, the existence of resources, the characteristics ofimplementing agents, the attitudes shown, the implementation of communication betweenorganizations and the environment. This is due to the lack of socialization of CentralMaluku Regency Regional Regulation no. 10 of 2022 which is the legal umbrella forregulating the determination of traditional villages. There are several obstacles inimplementing the determination of traditional villages in Central Maluku Regency,including the socialization of Regional Regulations and their implementing regulationsregarding the determination of traditional villages, the lack of references and studies oftraditional villages that are in accordance with the rights of origin and customary lawapplicable in Central Maluku Regency, and the lack of knowledge of government officialsand the community in determining traditional villages.